GEOCHEMICAL MARKERS OF THE JOINT STRUCTURAL AND COMPOSITIONAL EVOLUTION OF THE BASEMENT AND COVER (NORTHERN LADOGA SWECOFENNIDES, RUSSIA) - Yu. A. Morozov; E. N. Terekhov; M. A. Matveev; O. I. Okina (Геодинамика и тектонофизика)
Detailed studies of the deeply metamorphosed Early Precambrian rocks of the Northern Ladoga region allowed us to distinguish three deformation stages of the Svecofennian tectogenesis during which there occurred significant structural and compositional transformations of the "cover (Paleoproterozoic) – basement (Archean)" system. In addition to the structural-paragenetic analysis, which allowed to allocate transversal structural paragenesis in both floors, there are some other opportunities in the recognition of their-hosted granitoid veined bodies with a positive Eu anomaly. The rock varieties with this anomaly are always high in barium and do not show a direct correlation between the Eu anomaly and (La/Yb)n, Ca and Sr. This is contrary to the ideas about the occurrence of a positive Eu anomaly due to the substitution of divalent strontium by Eu++ and suggests that the formation of such rocks took place under the influence of deep reduced fluids. It was found that granitoids with a positive Eu anomaly were formed during the first and last stages of the structure evolution, with a predominance of brittle deformations and a deep-reduced fluid breakthrough. At the second stage, with the dominant manifestation of plastic deformations, when such fluids could be "blocked" within the system, there was a formation of granitoids with low barium concentrations and a negative Eu anomaly.